Technical competitiveness of nontraditional, fresh agricultural commodities, of costarrican exporters - Durán Quirós, Alfredo (2018)
An analysis of the concept of competitiveness was made, establishing it as a complex, multifactorial concept that covers various aspects such as factors related to each country, Government’s responsibility, aspects of private action, external to the company and internal aspects of the production system. “Technical competitiveness” is defined as “offering a product of excellent quality, low-cost and volume required by a specific market as a result of a technical management that seeks efficiency, innovation, productivity, loss and production costs reduction”. An analysis was made of the work performed by the authors in the development of a tool to quantify the technical competitiveness (called index of technical competitiveness (ICTE)), which consists of 12 groups of related items called “constructs”. The more relevant results of the national competitiveness diagnosis developed by authors in the year 2009 for the fruit, ornamentals, flowers, vegetables and roots and tubers sectors, are discussed indicating poor production conditions that limit the competitive ability of the enterprises. The effect of certifications on business development is also discussed, showing that companies which export to markets that require this type of certifications, have higher levels of technical business competitiveness index. In addition, the greater is the number of markets that one company supplies, the greater competitiveness index the company shows. Finally, the results of a training project developed on issues of competitiveness and development of improvement plans are discussed. Only 40% of companies that started the course were capable of finishing the training. All the managers recognized the importance of the training received, however, subsequently submitted assessments indicate that less than 20% of them has made improvements in their processes of operation or in the management of their human resources.